Antibiotics and Urinary Tract Infections - Truls E. Bjerklund Johansen (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Urinary tract infections (UTI) are one of the most frequently occurring infections, not only community acquired, but also hospital acquired infections. An increase of resistant uropathogens against commonly used antibiotics can be observed worldwide, a subject of great concern. Several strategies are discussed how to cope with this problem: i) not to use antibiotics, when not indicated, e.g. asymptomatic bacteriuria, or when non-antimicrobial measures are available, e.g. for prophylaxis of recurrent UTI; ii) to prefer even old antibiotics, which still have preserved their antibacterial activity against uropathogens; iii) if broad spectrum antibiotics are needed for empiric therapy of severe infections, to use the right and high enough dosages to reduce selection of resistant pathogens, and to step down to a more tailored antibiotic therapy as soon as possible; iv) to control and try to avoid health care associated UTI by optimal hygienic and interventional strategies; and last but not least v) to stimulate development of new antibiotics, especially when new bacterial targets can be approached